1996
DOI: 10.1159/000113224
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of Propatagial Musculature in a Flying Squirrel, <i>Glaucomys volans </i>(Rodentia, Sciuridae)

Abstract: The propatagium of gliding and flying mammals is of both functional and phylogenetic interest. The innervation of the propatagial muscle, platysma II, was studied with the axonal tracer wheat germ agglutinin-conjugated horseradish peroxidase (WGA-HRP) in a flying squirrel, Glaucomys volans. Injections of WGA-HRP into the proximal third of platysma II labeled motoneurons in the lateral part of the medial subdivision of the ipsilateral facial nucleus and in the ipsilateral ventral horn of the brachial enlargemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 16 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…Gait disorders, instability and falls have been reported to be the most common symptoms of PSP, both at the onset and during the course of the disease (table 2). Falls together with supranuclear opthalmoplegia are considered as mandatory for the diagnosis of PSP in the NINDS-SPSP criteria [17]. In our cohort, gait disorder and instability were present in all patients, whereas only 3 patients did not report multiple falls (although instability was reported in all 3 patients).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Gait disorders, instability and falls have been reported to be the most common symptoms of PSP, both at the onset and during the course of the disease (table 2). Falls together with supranuclear opthalmoplegia are considered as mandatory for the diagnosis of PSP in the NINDS-SPSP criteria [17]. In our cohort, gait disorder and instability were present in all patients, whereas only 3 patients did not report multiple falls (although instability was reported in all 3 patients).…”
Section: Discussionmentioning
confidence: 80%
“…Litvan et al [28] reported moderate to severe upward gaze palsy to be more frequent than downward abnormalities and suggested that upward gaze palsy in association with early gait instability and falls may be a better predictor of the disease. Other visual/ocular symptoms in PSP include diplopia, blurring of vision, light sensitivity, burning eyes, blepharospasm and eyelid apraxia [17, 24, 48]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical diagnoses of IPD and probable PSP were based on the UK Parkinson’s Disease Society Brain Bank clinical diagnostic criteria for PD [13] and the clinical criteria of the National Institute of Neurological Disorders and Stroke and Society for Progressive Supranuclear Palsy (NINDS-SPSP) [14]. Some PSP patients had only vertical gaze slowing at the time of initial examination, but eventually showed vertical gaze palsy at follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…There are at least two mechanisms that may help keep flow attached to the wing at higher angles of attack in flying squirrels. First is the presence of a propatagium, an extension of the wing membrane between the wrist and neck rostral to the forelimb (Chickering and Sokoloff, 1996). The propatagium can be oriented downward with respect to the rest of the wing membrane giving the wing a greater overall curvature, which can help to guide the flow more smoothly over the wing.…”
Section: Postural Adjustments Angle Of Attack and Stallmentioning
confidence: 99%